Development of Android-Based Interactive Multimedia to practice Critical Thinking Skills on Mutation Materials - Purwanti, Purwanti; Norra, Bunga Ihda; Purnamaningrum, Arifah (Jurnal Pendidikan MIPA, 2022)
The purpose of this study was to determine the feasibility and response of students to interactive multimedia based on android containing critical thinking skills on mutation material. This type of research is research and development (R&D), this research was developed using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The sample in this study were 10 students of MAN 2 Semarang. The results of the study: 76% of media experts, 81.81% of material experts, 90% of critical thinking experts, 91.61% of teacher responses, and 92.66% of student responses to interactive multimedia applications. Based on the results of the study, it can be concluded that android-based interactive multimedia to train critical thinking skills on mutasu material is very feasible to be used as teaching material. Keywords: critical thinking skills, interactive multimedia, development research. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp824-832